Bereavement and loss in older adulthood: associations between meaning-making, spirituality and grief - Sian, Chin Hui; Ismail, Asmah; Yusop, Yusni Mohamad; Ibrahim, Rahimah (Universiti Putra Malaysia, 2024)
Losing a loved one in older adulthood affects one's emotional well-being profoundly. The grief experienced by older adults, who may have shared significant experiences and memories with their loved ones, can be intensified by cumulative losses and is often not acknowledged by themselves or their caregivers. This study uses a descriptive quantitative cross-sectional design to determine the relationships between potential predictors and grief among older adults. This cross-sectional study uses purposive sampling and involves 134 older adults aged 60 years or above who had experienced significant loss within the past 60 months. A self-administered questionnaire assessed participants' demographic characteristics, loss experiences, grief, spirituality, and meaning-making. Multiple linear regression analysis was carried out to determine the significant predictors of meaning-making and spirituality regarding grief. The findings indicated significant negative associations between spirituality, meaning-making, and grief. This study emphasizes the importance of addressing the spiritual and meaning-making dimensions in supporting older adults in effectively managing grief-related distress. Future studies should consider longitudinal designs and further explore additional predictors to provide a more comprehensive understanding of the complex factors influencing grief and the healing process.